2007
DOI: 10.1063/1.2713769
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hysteresis and scaling behavior of hard lead zirconate titanate bulk ceramics

Abstract: The scaling relation of ferroelectric hysteresis area ⟨A⟩ against frequency f and field amplitude E0 for the saturated loops of the hard lead zirconate titanate bulk ceramic takes the form of ⟨A⟩∝f−0.28E00.89, while that for the minor loops takes the form of ⟨A⟩∝f−0.43E03.19. In both cases, the scaling relations are similar to those of its soft counterpart. This indicates that the dynamic behaviors and scaling relations in bulk ceramics are mainly governed by the domain states and structures, while the distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 22 publications
4
52
1
Order By: Relevance
“…4 and 5) that at a given carbon content the dissipation energy is seen to increase with both the electric field amplitude and frequency. An increase of the loop area with electric field amplitude is intuitively expected, as has also been reported in several previous investigations [27][28][29][30]. The nearly linear increase of the loop area with the frequency is, on the other hand, unexpected.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…4 and 5) that at a given carbon content the dissipation energy is seen to increase with both the electric field amplitude and frequency. An increase of the loop area with electric field amplitude is intuitively expected, as has also been reported in several previous investigations [27][28][29][30]. The nearly linear increase of the loop area with the frequency is, on the other hand, unexpected.…”
Section: Resultssupporting
confidence: 64%
“…The nearly linear increase of the loop area with the frequency is, on the other hand, unexpected. Generally, in ferroelectric ceramics, the observation, which the loop area decreases with increasing frequency, is ascribed to the delayed response of the polarization reversal to the varying external field [27][28][29][30]. However, the increase of the loop area, with increasing frequency, observed in the present study, is not fully understood, but could be attributed to the presence of the conducting carbon phase in the composites.…”
Section: Resultscontrasting
confidence: 59%
“…Previous investigations have reported the scaling relations in thin films [5,6], soft PZT, hard PZT and 95PbZrO 3 -5PbTiO 3 (PZT95/5) bulk ceramics [7][8][9], and BaTiO 3 single crystals [10]. The scaling behavior of dynamic hysteresis revealed that the relation between A and E 0 , f was different in two different field stages (low-E 0 and high-E 0 ) [7,8,10].…”
Section: Introductionmentioning
confidence: 96%
“…The scaling behavior of dynamic hysteresis revealed that the relation between A and E 0 , f was different in two different field stages (low-E 0 and high-E 0 ) [7,8,10]. While Viehland had pointed out that polarization reversal behaviors were different in three different stages of external electric field, e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Several variables may cause the delay in domain switching including charged defects and space charges. 41 The polarization and hysteresis area ͗A͘ decrease rapidly with increase in negative coefficient of m. On the other hand, if exponent m has lower negative coefficient, this implies that the switching time is short. The ferroelectric domains can follow the applied ac electric field, so the polarization and hysteresis area ͗A͘ decreases slowly.…”
Section: Dynamic Scaling Relationshipsmentioning
confidence: 98%